Choreographed Footfalls. Issue 1 (April 2018) - Revely-Calder, Cal
Abstract : In Samuel Beckett's play Footfalls, a woman called 'May' walks back and forth. In this essay, I suggest that the play's physical plainness may be its most difficult aspect: Footfalls is a prime example of how Beckett's later plays are more like enigmas than riddles, frustrating us without an eventual solution. As we try to describe and interpret May's motions, we're continually repelled, and denied the critical certainty we might want. But that desire may be the wrong one to have; instead, I would venture that the play's careful choreography is both the thing that's expressive, and the thing being expressed. Focusing on this choreographic metaphor, and drawing on dance practitioners and theorists from Lucia Ruprecht to Merce Cunningham, I suggest that Footfalls is about itself, which is to say that it's about 'about-ness' – how we search for words to describe motions that seem resistant to paraphrase. In the late 1970s, Beckett was certainly interested in dance. This wasn't evident only in the case of Billie Whitelaw and Footfalls . Directing Come and Go (as Kommen und Gehen ) in 1978, Beckett wanted the performers' shoes to be 'genre ballerine'; writing Quad in 1980, he specified that 'some ballet training' on the performers' part was 'desirable'. I caution against misreading these plays as dances – they are not – but suggest that corporeal discipline was something with which Beckett became fixated. And this wasn't only a matter of stagecraft, as we can see by reading the late poetic sequence mirlitonnades, written in French between 1976 and 1980 – the period in which Beckett finished both Footfalls and its French sibling Pas . These poems are tightly linked to the plays alongside which they were written; the link, in David Wheatley's phrase, can be seen in their 'harnessing of speech to carefully choreographed movement'. The mirlitonnades place a repeated emphasis upon their rhythms, and the ways in which they intimate physical movement without literally enacting it. This is so because, as Eric Griffiths puts it, 'the reader must inform writing with a sense of the writer it calls up – an ideal body, a plausible voice'. In Beckett's later work, I suggest, he was attentive to how the conjunction of body and voice appeared, as much as how it meant – and he wanted to augment the difficulties that this poses for his critics' task.